Clinical Outcome Success of Silver-Modified Atraumatic Restorative Treatment (SMART) in Treating Children with Dental Caries in Primary Teeth: A Systematic Review - Mohapatra, Subhashree; Mohandas, Rahul (Journal of Health and Allied Sciences NU, 2024)
Objective: A novel approach called silver-modified atraumatic restorative therapy (SMART) integrates glass ionomer cement (GIC) restorations with silver diamine fluoride (SDF). This new method combines the ability of GIC to seal the tooth and sever the nutrition that bacteria require to proliferate, with the bactericidal power of SDF. The purpose of this review is to evaluate and compare the available data regarding the efficacy of the SMART approach in treating children's carious primary teeth.Materials and Methods: The earliest date accessible up until February 15, 2024, was thoroughly searched in databases including Scopus, PubMed, Cochrane, Science Direct, Lilacs, Science Direct, Web of Science, and Google Scholar. The review only comprised randomized controlled trials. The PICO strategy (P: Children with dental caries in primary teeth; I: SMART; C: Conventional drill and fill method or atraumatic restorative treatment [ART] therapy; O: Clinical success) was adopted. Risk of bias assessment and quality of evidence were assessed using the RoB-2 tool and GRADE tool, respectively.Results: Four full-text publications that met the eligibility criteria underwent additional processing for data extraction and qualitative analysis. In three studies, no difference was found in the clinical performance of SMART and conventional drill and fill/ART therapy, whereas in one study, the clinical performance of SMART was found to be better than the conventional ART therapy.Conclusion: SMART and conventional drill and fill/ART techniques have comparable clinical performance for carious primary teeth of children. SMART can be used to treat asymptomatic deep carious lesions as well as apprehensive children. However, the cost-effectiveness of SMART restorations needs to be investigated in a variety of demographics.
Keywords: treatment outcome; dental atraumatic restorative treatment; dental restoration; dental caries; tooth deciduous; silver diamine fluoride